Following Spinoza’s conjecture and image: Representativeness and availability as generators of conscious errors in space and time - Mounitz, Abraham (Edelweiss Applied Science and Technology, 2024)
The article will present an intertextual encounter between Spinoza’s approach and the work of Kahneman and others. on cognitive bias. The discussion will focus on the link between imagination and memory and space and time as well as the former’s association with representativeness, availability, and occasion noise as the causes of bias in both systems of thought. Spinoza determined that the manner of human thought has common traits but also that there is thought which accords with reality alongside thought which is erroneous. Like Spinoza, contemporary theory also seeks to address the causes of such erroneous thought and to offer remedies for its prevention.